2019
DOI: 10.30872/psikostudia.v7i2.2402
|View full text |Cite
|
Sign up to set email alerts
|

Peran Role Model Dalam Membentuk Perilaku Pro-Lingkungan

Abstract: This research is a qualitative research with a phenomenological approach which aims to determine the role of role models in shaping pro-environment behavior. The subjects in this study were 4 people and there were 5 informants who had been selected according to the established characteristics, namely individuals who care about the surrounding environment and are active in environmental organizations. Methods of collecting data using observation and interviews. The results of this study show that pro-environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
3
0
8
Order By: Relevance
“…Based on this, it could be seen that the research subjects, namely undergraduate students, were still required to increase their awareness of the environment with a more substantial effort to be able to carry out proenvironmental behavior such as those related to purchasing environmentally friendly goods and efforts to recycle environmentally friendly goods. Rifayanti et al (2018), in their research, revealed that role models were needed to be able to influence someone in carrying out proenvironmental behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, it could be seen that the research subjects, namely undergraduate students, were still required to increase their awareness of the environment with a more substantial effort to be able to carry out proenvironmental behavior such as those related to purchasing environmentally friendly goods and efforts to recycle environmentally friendly goods. Rifayanti et al (2018), in their research, revealed that role models were needed to be able to influence someone in carrying out proenvironmental behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Pemahaman yang dimiliki diharapkan dapat membantu dalam membentuk perilaku pro-lingkungan. Hal tersebut diperkuat penelitian Martini (2019;Rifayanti et al, (2019), yang menyatakan pengetahuan dan pemahaman dapat membentuk perilaku pro-lingkungan jika memperhatikan instrumen evaluasi yang tepat.…”
Section: Pengaruh Interaksi Media Pembelajaran Dan Gender Terhadap Pe...unclassified
“…Cara guru menjelaskan mengenai peraturan main, kegiatan, tugas untuk anak dengan gangguan pendengaran adalah menjadi role model. Role model merupakan sesuatu yang perilakunya dapat ditiru (Rifayanti et al, 2018). Jadi guru harus memperagakan apa yang akan menjadi tugas atau kegiatan bagi anak.…”
Section: Cara Guru Memberikan Atau Menjelaskan Mengenai Peraturan Main Kegiatan Tugas Untuk Anak Dengan Gangguan Pendengaranunclassified